Evaluating ex vivo toll-like receptor agonist response as a potential biomarker in equine gastric ulcer syndrome - Gustavo Ferlini Agne; Daniel Thomas Barratt; Bridget Eileen May; Mark R. Hutchinson; Joshua Holmes; Catherine Steel; Olivier Simon; Samuel Greig Evans; Andrew A. Somogyi; Benjamin W. Sykes; Samantha Franklin (The Veterinary Journal, 2026)

Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

A systematic review and meta-analysis of randomised control trials examining the impact ultra-processed vs. less processed food has on energy intake and body weight - Eric Robinson; Jane Brealey; Jenna R. Cummings; Rebecca Evans; Amy Finlay; Esther Fisher; Thomas Gough; Andrew Jones; Madeleine Jutla; Euba Morenikeji-Ibilola; Victoria Norton (Appetite, 2026)

Contribution of the Loire River to knowledge about hungry Rivers – Three centuries of a lowland river trajectory - Emmanuèle Gautier; Evan Mesmin; Clément Virmoux; Thomas Dépret; Ségolène Saulnier-Copard; Gilles Arnaud-Fassetta; Guillaume Martins; Valentine Fichet; Stéphane Braud (Geomorphology, 2026)

Are we underfitting dinosaur growth models? Accounting for intra- & interspecific variation - Evan Thomas Saitta (Cretaceous Research, 2026)

Advancing continuous in-situ quantification of microbial contamination in environmental waters using tryptophan-like fluorescence—Sensor design and validation - Whitney Knopp; Joshua Klaus; Danny Wilson; Michael J. Vlah; Matthew R.V. Ross; Evan Thomas (Water Research, 2026)

Optimized LCZ mapping with automated machine learning reveals thermal disparities during a heatwave event - Jiyang Xia; Yuan Sun; Fenghua Ling; Sarah Lindley; Jianyi Liu; Xinyue Ye; Thomas J. Bannan; James Evans; David O. Topping; Lei Bai; Zhonghua Zheng (Urban Climate, 2026)

Work Safety Climate, Heat-Related Illness, and Potential Pesticide Exposure Among Latino Farmworker Adolescents and Young Adults in Arizona - Fiorella L. Carlos Chavez; Priscilla Carmiol-Rodríguez; Taylor J. Arnold; Keenan A. Pituch; Evan P. Anderson; Amber Wutich; Alexandra Brewis; David W. Coon; Thomas A. Arcury (Journal of Agromedicine, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Dynamic Phenology of Canopy-Forming Macroalgal Forests within a Tropical Seascape - Shaun K. Wilson; Christopher J. Fulton; Martial Depczynski; Ben Radford; Thomas H. Holmes; Matthew Birt; Cal Faubel; Marjetta L. Puotinen; Mae Noble; Richard D. Evans; Molly Moustaka; Paul Tinkler; et al. (Ecosystems, 2026)
Biomass dynamics of primary producers provide a basis for assessing their capacity to capture carbon and mitigate excess greenhouse gases. Here, we estimate inter-annual and seasonal biomass cycles in canopy-forming Sargassaceae at 19 sites spanning ~ 200 km of the Ningaloo World Heritage Area over 11 consecutive years. Our global average summer estimate of 1.53 kg wet wt m −2 equates to 4.1–9.4 Gg of standing macroalgal carbon (14.9–34.6 Gg CO 2 ) across 38,300 ha of all macroalgae habitats. Biomass estimates did not differ significantly among years but varied by an order of magnitude among sites. Accumulation typically occurred during the spring, followed by a loss of 42–94 Gg wet weight, or 1.4–3.3 Gg organic carbon (5.3–12.0 Gg CO 2 ) fixed in macroalgal habitats during autumn. Seasonal patterns of biomass accumulation and release were, however, spatially and temporally variable, some sites accumulating biomass in autumn and releasing it during the following spring. Spring biomass accumulation was reduced by herbivorous urchins, whilst the extent of macroalgae biomass change in the autumn was directly correlated with sea temperature and standing biomass the previous summer. These findings imply canopy-forming macroalgae provide a regular injection of biomass into the surrounding ecosystems, which support productivity of surrounding habitats and is a potential source of organic carbon for burial in carbon sinks throughout the year. Modelling that seeks to link macroalgae sources with sinks therefore requires a spatially explicit understanding of when seasonal senescence of canopy-forming macroalgae occurs, inter-site variability and the environmental conditions that govern this phenology.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Evaluating the use of uncrewed surface vessels to enhance Lake Erie acoustic prey-fish surveys. - Mark R. DuFour; Thomas M. Evans; Lars G. Rudstam; Suresh A. Sethi; Jeremy P. Holden; Heather Luken; Peter Jenkins; Daniel L. Yule; David M. Warner; Steven A. Farha; Timothy P. O’Brien; Andrew R. Barnard; et al. (Fisheries Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Population genetic and phylogenetic analysis of pupfish (Cyprinodon, Cyprinodontidae) in the Rio Conchos and adjacent rivers reveals hidden diversity - Casey Ernest; Michael Tobler; Ma. Lourdes De Lozano-Vilano; Mauricio De La Maza-Benignos; Tracy A. Diver; Wade D. Wilson; Thomas F. Turner; Evan W. Carson (Conservation Genetics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Comparing Influences of Natural and Artificial Woody Habitat on Benthic Macroinvertebrates in a North Temperate Lake - Matthew P. Woo; Thomas M. Detmer; Montana E. Airey; Stephen F. Jane; Dov F. Sax; Evan Dlugos; Emma G. Menard; Julián Torres-Dowdall; Peter B. McIntyre (Hydrobiologia, 2026)
Littoral habitat is an important organizing force in lacustrine food webs. Modification of littoral habitat directly impacts aquatic macroinvertebrates, which are important vectors between basal resources and higher trophic levels. Lakeshore residential development is a pervasive phenomenon often characterized by the loss of coarse woody habitat (CWH) from lakes, and the construction of artificial wooden structures (docks and ramps). To characterize the effects of artificial wooden structures on macroinvertebrate spatial distributions, we surveyed assemblages across a lightly developed lake in New York’s Adirondack Park. Using benthic sweeps and Hester-Dendy samplers, we sampled assemblages at both natural CWH and artificial wooden structures (boat ramps), and compared them to those in adjacent, non-woody areas. We found that both CWH and artificial wooden structures facilitated larger, more complex assemblages than non-woody areas. We additionally considered general shoreline characteristics, and found only compositional effects on assemblages. We suggest that impacts on aquatic macroinvertebrates arise at a fine spatial scale, and find evidence that development-associated CWH loss drives macroinvertebrate depletion. Although CWH and artificial wooden structures are unlikely to be equivalent at whole-lake scales, macroinvertebrate depletion may be functionally alleviated at fine scales by the construction of artificial wooden structures such as ramps.

Comparing the impact of feedback on excess calories and physical activity calorie equivalent (PACE) information on consumer behaviour in an online hypothetical restaurant setting - Andrew Jones; Thomas Gough; Rebecca Evans; Amy Finlay; Jay J. Duckworth; Sam Burton; Abigail K. Rose; Eric Robinson (Appetite, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

A new approach improving koala habitat prediction using hyperspectral airborne imagery - Cristian Gabriel Orlando; Floris Van Ogtrop; Thomas F.A. Bishop; Bradley J. Evans; Terry Cocks; Jose I.N. Gallegos; Mathew S. Crowther (Science of The Total Environment, 2025)

Estimating PM2.5 in Fort Collins, Colorado using a robust drive-by correction of low-cost air quality monitors deployed on school buses - Priyanka deSouza; Jessa Ellenburg; Andrew Turnipseed; Craig Williford; Helena Pliszka; Story Schwantes; Timothy Dye; Luke Greenidge; Austin Bailly; Thomas Kopala; Evan Vaughan; Michael Samon; et al. (Science of The Total Environment, 2025)

Persistent urinary metabolic signatures in children with type 1 diabetes - Ernesto S. Nakayasu; Javier E. Flores; Lisa M. Bramer; Jackson L. Chin; Young-Mo Kim; Farooq Syed; Erika M. Zink; Brigitte I. Frohnert; Carmella Evans-Molina; Paul B. Kaplowitz; Fran E. Cogen; Rembert Pieper; et al. (Next Research, 2025)

Management of alien bird impacts does not reflect their severity - Thomas Evans; Ross N. Cuthbert (Journal of Environmental Management, 2025)

Recent Crop‐To‐Weed Adaptive Introgression Has Reshaped the Genomic Composition and Geographical Structure of US Weedy Rice ( Oryza spp.) - Marshall J. Wedger; Evan Xiao; Thomas R. Butts; Justin L. Chlapecka; L. Connor Webster; Kenneth M. Olsen (Molecular Ecology, 2025)
Weedy rice is a close relative of cultivated rice ( Oryza sativa ) that infests rice fields worldwide and drastically reduces yields. To combat this agricultural pest, rice farmers in the southern US began to grow herbicide‐resistant (HR) rice cultivars in the early 2000s, which permitted the application of herbicides that selectively targeted weedy rice without harming the crop. The widespread adoption of HR rice coincided with increased reliance on hybrid rice cultivars in place of traditional inbred varieties. Although both cultivated and weedy rice are predominantly self‐fertilising, the combined introductions of HR and hybrid rice dramatically altered the opportunities and selective pressure for crop‐weed hybridization and adaptive introgression. In this study, we generated genotyping‐by‐sequencing data for 178 weedy rice samples collected from across the rice growing region of the southern US; these were analysed together with previously published rice and weedy rice genome sequences to determine the recent genomic and population genetic consequences of adaptive introgression and selection for herbicide resistance in US weedy rice populations. We find a reshaped geographical structure of southern US weedy rice as well as purging of crop‐derived alleles in some weed strains of crop‐weed hybrid origin. Furthermore, we uncover evidence that related weedy rice strains have made use of different genetic mechanisms to respond to selection. Lastly, we identify widespread presence of HR alleles in both hybrid‐derived and nonadmixed samples, which further supports an overall picture of weedy rice evolution and adaptation through diverse genetic mechanisms.

‘State of the Environment’ reports require integrated and holistic approaches – Lessons from Australia’s marine experience - Rowan Trebilco; Cass Hunter; Mibu Fischer; Karen Evans; Alistair J. Hobday; Linda Thomas (Marine Policy, 2025)

Naturally deformed polymineralic rocks provide quantitative rheological information - Kyrsten L. Johnston; Laurel Goodwin; Basil Tikoff; Evan Earnest; Christine Gopon; Thomas G. Blenkinsop (Journal of Structural Geology, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Food in the news: effects of exposure to information about ultra-processed vs. high in nutrients of concern foods on consumer perceptions and intake - Thomas Gough; Jenna R. Cummings; Rebecca Evans; Scott Hill; Andrew Jones; Eric Robinson (Appetite, 2025)

Earliest trace fossil evidence of wood-eating termites (Isoptera) and mites (Oribatida) in circumpolar environments of Australia - Juliana Edwards; Anthony J. Martin; William M.G. Parker; Melissa Lowery; Ankit Dodla; Magdalena Giergiel; Callum Gassner; Bayden R. Wood; Thomas H. Rich; Alistair R. Evans; Patricia Vickers-Rich (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Food grade titanium dioxide is related to gut dysbiosis, but not markers of intestinal inflammation nor permeability in healthy, young adults - Lisa C. Merrill; Evan Thomas; Justin R. Wright; Regina Lamendella; Suresh Bhandari; Dhimiter Bello; Shannon L. Kelleher; Katherine L. Tucker; Kelsey M. Mangano (NanoImpact, 2025)

Long-term Deepwater Dissolved Oxygen Dynamics in a Hypereutrophic Reservoir Following Shifts in Watershed Management and Lake Warming - Lesley B. Knoll; Thomas J. Fisher; Michael J. Vanni; Evan G. Youngblade (Ecosystems, 2025)
Long-term declines in lake hypolimnetic dissolved oxygen (DO) have been attributed to eutrophication, reduced water clarity, or rising temperatures. DO dynamics in human-made reservoirs may also be influenced by their distinct characteristics (for example, hydrology) and by the high levels of watershed inputs (suspended sediments, nutrients) these systems may receive, particularly in agricultural landscapes. We used a 31 year dataset in a reservoir that has experienced agricultural land management change to ask: (1) What are the long-term trends in two hypolimnetic DO metrics (DO concentration in early summer and summer anoxic factor), and (2) what are the key drivers of these metrics?. We used linear regressions to assess temporal trends, and exhaustive variable selection to identify drivers. Potential drivers included metrics of watershed discharge, temperature, stability, and potential productivity (chlorophyll, nonvolatile suspended sediments; NVSS). We found that deepwater early summer DO concentrations decreased, but there was no temporal trend for anoxic factor. Deepwater DO was best predicted by surface temperature, with warming temperatures related to lower DO. However, the top five models performed similarly, and all included a temperature or stratification metric. Higher stability was related to lower DO. For anoxic factor, the top two models performed similarly with stability, surface temperature, and NVSS identified. Anoxic factor increased with higher surface temperature, lower NVSS, and higher stability. Our findings suggest that DO dynamics were linked to previously recognized drivers (for example, temperature), as well as NVSS, a driver that is rarely acknowledged and may reflect land use and management within the watershed.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Growth Patterns Between Ages 0 and 36 Months Among US Children With Orofacial Cleft: A Retrospective Cohort Study - Christy M. McKinney; Waylon Howard; Kiley Bijlani; Muhammad Rahman; Anna Meehan; Kelly N. Evans; Dawn Leavitt; Thomas J. Sitzman; Peter Amoako-Yirenkyi; Carrie L. Heike (Journal of the Academy of Nutrition and Dietetics, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Sensor-measured versus reported latrine use to characterize sanitation intervention uptake in a randomized controlled trial among households in rural Bangladesh - Mahfuza Islam; Jesse D. Contreras; Leanne Unicomb; Mahbubur Rahman; Benjamin F. Arnold; John M. Colford; Stephen P. Luby; Evan A. Thomas; Ayse Ercumen (International Journal of Hygiene and Environmental Health, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Ocean crustal veins record dynamic interplay between plate-cooling-induced cracking and ocean chemistry - Aled D. Evans; Rosalind M. Coggon; Michelle Harris; Elliot J. Carter; Elmar Albers; Gilles M. Guérin; Thomas M. Belgrano; Mallika Jonnalagadda; Lewis J.C. Grant; Pamela D. Kempton; David J. Sanderson; James A. Milton; et al. (Earth and Planetary Science Letters, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Inter-annual variation in movements and passage of seaward migrating European eels at a shrouded Archimedean screw pumping station - Oliver J. Evans; Liam J. Carter; Thomas Hutchinson; Andrew Don; Rosalind M. Wright; Henrik Baktoft; Ine S. Pauwels; Jonathan D. Bolland (Ecological Engineering, 2024)

Efficient continuous Energy-Multigroup hybrid depletion scheme using the Shift Monte Carlo code. Part I: Energy condensation sensitivity analysis - Vidor H. Lujan; Bailey Painter; Inhyung Kim; Massimiliano Fratoni; Thomas M. Evans; Tara M. Pandya; Dan Kotlyar (Annals of Nuclear Energy, 2024)

Exploring maternal and developmental toxicity of perfluoroalkyl ether acids PFO4DA and PFO5DoA using hepatic transcriptomics and serum metabolomics - Thomas W. Jackson; Christy S. Lambright; Nicola Evans; Leah C. Wehmas; Denise K. MacMillan; Jacqueline Bangma; L. Earl Gray; Justin M. Conley (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Corrigendum to ‘Evaluating the effect of expert elicitation techniques on population status assessment in the face of large uncertainty’ [J. Environ. Manag. 306 (2022) /114453] - Jennifer F. Moore; Julien Martin; Hardin Waddle; Evan H. Campbell Grant; Jill Fleming; Eve Bohnett; Thomas S.B. Akre; Donald J. Brown; Michael T. Jones; Jessica R. Meck; Kevin Oxenrider; Anthony Tur; et al. (Journal of Environmental Management, 2024)

Peering into the eye of the sea lamprey: what can stable isotopes in lamprey eye lenses reveal about their life history? - Thomas M. Evans; Joseph Zydlewski (Environmental Biology of Fishes, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Symbiont community dynamics in the turbid reef specialist, Turbinaria reniformis, along a latitudinal and environmental gradient in Western Australia - Adi Zweifler; Richard D. Evans; Nicola K. Browne; Luke Thomas (Coral Reefs, 2024)
Thermal stress triggers the breakdown of the obligate symbiosis between the cnidarian coral host and its autotrophic dinoflagellates of the family Symbiodiniaceae. This diverse family exhibits pronounced functional variation that has large implications for the survival of their coral host. In this study, we explored patterns of symbiont community composition and diversity in the coral Turbinaria reniformis , a turbid reef specialist, along a latitudinal and environmental gradient in Western Australia. Using metabarcoding of the internal transcribed spacer region 2, we explored symbiont community patterns, their environmental drivers, and potential associations with host genetic structure. Our findings reveal a predominance of Cladocopium across our study area, with distinct regional composition influenced primarily by sea surface temperature. Geographical distance and host genetic data did not align with symbiont community divergence, suggesting a complex interplay of environmental and genetic factors t shaping the community structure. This study underscores Cladocopium stability in Western Australia across large distances and strong environmental gradients. It also highlights the highly diversified lineage community that may explain T. reniformis ability to thrive in a wide range of environmental conditions.

Post‐release mortality of line‐caught snapper Chrysophrys auratus depends on hook site and capture depth - Jade Q. Maggs; Oliver Evans; John C. Holdsworth; Thomas Lumley; Bruce W. Hartill (Fisheries Management and Ecology, 2024)
Catch‐and‐release angling is common in recreational fisheries, but post‐release mortality (PRM) may be high. We conducted a controlled field experiment to estimate mortality of released snapper Chrysophrys auratus . Recreational fishers caught 960 snapper from three depth strata (

Can juvenile supply predict future abundance of large-bodied reef fishes? - Shaun K. Wilson; Martial Depczynski; Christopher J. Fulton; Thomas H. Holmes; Jordan S. Goetze; Matthew J. Birt; Ben Radford; Paul Tinkler; Richard D. Evans; Molly Moustaka; Cal Faubel; Mae Noble (Marine Environmental Research, 2024)

The early onset of magmatic rift faulting in the Edward-George Rift, Uganda - Luke N.J. Wedmore; Dan Evans; Jack N. Williams; Juliet Biggs; Åke Fagereng; Peter Mawejje; Fred Tugume; Thomas Blenkinsop; Daniel E.J. Hobley (Earth and Planetary Science Letters, 2024)

Is EGD Needed in all Patients after Suicidal or Exploratory Caustic Ingestions? - Michael Levine; Yaron Finkelstein; William J. Trautman; Dazhe Cao; Evan Schwarz; Ari Filip; Leanne Cook; Sameer Arbussattar Pathan; Cherie Obilom; Jim Liu; Joseph Yanta; Neta Cohen; et al. (Journal of Medical Toxicology, 2024)

A warming western boundary current increases the prevalence of commercially disruptive parasites in broadbill swordfish - Jessica A. Bolin; Karen Evans; David S. Schoeman; Claire M. Spillman; Thomas S. Moore; Jason R. Hartog; Scott F. Cummins; Kylie L. Scales (Fisheries Oceanography, 2024)
Meat quality is of paramount importance in the fisheries and aquaculture industries, but the quality of seafood can be affected by environmental variability and change, creating uncertainties in the delivery of consistent, high‐end product. Reports from fishers operating in an Australian fishery catching broadbill swordfish ( Xiphias gladius ) suggest that anomalously warm waters are linked with myoliquefaction of muscle tissue. The condition affects the marketability of fish by turning the meat into a soft, mushy texture post‐mortem and is caused by infection by the myxozoan parasite Kudoa musculoliquefaciens . Here, we combine microscopy, molecular techniques and ecological modelling to explore potential environmental drivers of the prevalence and intensity of K. musculoliquefaciens in swordfish, as a first step in understanding how a warming ocean might exacerbate the risk of harvesting an infected swordfish and the resultant potential risk of myoliquefaction. We develop predictive dynamic risk surfaces on seasonal timescales, with results revealing both the likelihood of harvesting an infected swordfish and the intensity of parasite load increase during the Austral summer. The prevalence of the parasite further increases in the region dominated by the East Australian Current, when locally warm areas are atypically cool and when average monthly temperatures are more variable. These findings provide information useful in predicting the conditions under which the risk of harvesting infected swordfish might be intensified, enabling adaptation to climate change impacts and optimisation of decision‐making when fishing under risky conditions.

Greener leaves from northern trees: Latitudinal compensation in riparian cottonwoods - Sobadini Kaluthota; David W. Pearce; Luke M. Evans; Thomas G. Whitham; Stewart B. Rood (Forest Ecology and Management, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Corrigendum to “Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays” [920 (2024) 171053] - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Global introductions and environmental impacts of freshwater megafish - Xing Chen; Thomas G. Evans; Jonathan M. Jeschke; Sonja C. Jähnig; Fengzhi He (Global Change Biology, 2024)
Freshwater megafish species, such as sturgeons, salmonids, carps, and catfishes, have a maximum reported weight ≥30 kg. Due to their charisma and economic value, they have been widely introduced outside of their native ranges. Here, we provide a comprehensive overview of the introduction of freshwater megafish and an assessment of their environmental impacts. Of the 134 extant freshwater megafish species, 46% have been introduced to new environments, and of these, 69% have established self‐sustaining alien populations. These introductions affect 59% of the world's main basins, with the USA and western Europe being particular hotspots of megafish introductions. The common carp ( Cyprinus carpio ) is the most widely introduced species. Using the Environmental Impact Classification for Alien Taxa (EICAT and EICAT+) frameworks, we assessed the severity and type of negative and positive impacts posed by alien megafish on native species. Alien megafish caused negative impacts through nine different mechanisms, with predation being the most frequently reported mechanism, followed by herbivory and competition. Moreover, 58% of the alien megafish species with sufficient data to evaluate the severity of their impacts caused declining populations of native species, or worse, extirpations of native species populations. The positive environmental impacts of alien megafish were far less frequently documented. They include biotic interactions that benefit native species, and the provision of trophic resources or habitats. Widely introduced or extensively studied species are more likely to have documented severe impacts on native species. There is a clear trade‐off between the economic benefits associated with megafish introductions and the severe adverse impacts they have on native biodiversity. Our study highlights the need for comprehensive risk assessments to evaluate the potential environmental impacts of megafish. More research and long‐term monitoring schemes are required to inform management actions to protect biodiversity, particularly in the Global South.

Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision‐making - Sabrina Kumschick; Sandro Bertolino; Tim M. Blackburn; Giuseppe Brundu; Katie E. Costello; Maarten de Groot; Thomas Evans; Belinda Gallardo; Piero Genovesi; Tanushri Govender; Jonathan M. Jeschke; Katharina Lapin; et al. (Conservation Biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision‐making procedures, making it a particularly relevant resource for addressing the impact of non‐native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species’ impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non‐native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non‐native species has led to devastating consequences for human well‐being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non‐native species and meeting and monitoring progress toward the Kunming–Montreal Global Biodiversity Framework (GBF) Target 6.

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Exploring the microbial diversity of novel misos with metagenomics - Caroline Isabel Kothe; Jacob Agerbo Rasmussen; Sarah S.T. Mak; M. Thomas P. Gilbert; Joshua Evans (Food Microbiology, 2024)

Non-avian dinosaur eggshell calcite can contain ancient, endogenous amino acids - Evan T. Saitta; Jakob Vinther; Molly K. Crisp; Geoffrey D. Abbott; Lucy Wheeler; Samantha Presslee; Thomas G. Kaye; Ian Bull; Ian Fletcher; Xinqi Chen; Daniel Vidal; Fernando Sanguino; et al. (Geochimica et Cosmochimica Acta, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Timing is everything; operational changes at a pumping station with a gravity sluice to provide safe downstream passage for silver European eels and deliver considerable financial savings - Liam J. Carter; Rosalind M. Wright; Robert E. Thomas; Jake Reeds; Leona A. Murphy; Stephen J. Collier; Oliver Evans; Henrik Baktoft; Jonathan D. Bolland (Journal of Environmental Management, 2023)

Collective and harmonized high throughput barcoding of insular arthropod biodiversity: Toward a Genomic Observatories Network for islands - Brent C. Emerson; Paulo A. V. Borges; Pedro Cardoso; Peter Convey; Jeremy R. deWaard; Evan P. Economo; Rosemary G. Gillespie; Susan Kennedy; Henrik Krehenwinkel; Rudolf Meier; George K. Roderick; Dominique Strasberg; et al. (Molecular Ecology, 2023)
Current understanding of ecological and evolutionary processes underlying island biodiversity is heavily shaped by empirical data from plants and birds, although arthropods comprise the overwhelming majority of known animal species, and as such can provide key insights into processes governing biodiversity. Novel high throughput sequencing (HTS) approaches are now emerging as powerful tools to overcome limitations in the availability of arthropod biodiversity data, and hence provide insights into these processes. Here, we explored how these tools might be most effectively exploited for comprehensive and comparable inventory and monitoring of insular arthropod biodiversity. We first reviewed the strengths, limitations and potential synergies among existing approaches of high throughput barcode sequencing. We considered how this could be complemented with deep learning approaches applied to image analysis to study arthropod biodiversity. We then explored how these approaches could be implemented within the framework of an island Genomic Observatories Network (iGON) for the advancement of fundamental and applied understanding of island biodiversity. To this end, we identified seven island biology themes at the interface of ecology, evolution and conservation biology, within which collective and harmonized efforts in HTS arthropod inventory could yield significant advances in island biodiversity research.

Fish avoidance of ships during acoustic surveys tested with quiet uncrewed surface vessels - Thomas M. Evans; Lars G. Rudstam; Suresh A. Sethi; David M. Warner; S. Dale Hanson; Benjamin Turschak; Steven A. Farha; Andrew R. Barnard; Daniel L. Yule; Mark R. DuFour; Timothy P. O’Brien; Kevin N. McDonnell; et al. (Fisheries Research, 2023)

Green and gold kiwifruit powders consumed for 28 days by healthy individuals with occasional constipation are safe and well-tolerated: A randomized controlled trial - Erin D. Lewis; David C. Crowley; Rupal Trivedi; Thomas Wolever; Mary Ann Buggia; Emma Graham; Starin McKeen; Jennifer Gu; Doug Rosendale; Malkanthi Evans (Bioactive Carbohydrates and Dietary Fibre, 2023)

Bilateral Cerebellar Repetitive Transcranial Magnetic Stimulation for Chronic Ataxia After Hemorrhagic Stroke: a Case Report - Evan Hy Einstein; Juliana Corlier; Cole Matthews; Doan Ngo; Michael K. Leuchter; Cole Citrenbaum; Nikita Vince-Cruz; Bhavna Ramesh; Aaron Slan; Scott A. Wilke; Nathaniel Ginder; Thomas Strouse; et al. (The Cerebellum, 2023)

A synthesis of approaches to support integrated assessments of hazards for the emerging Blue Economy - M.P. Turschwell; E.A. Fulton; J. Melbourne-Thomas; M. Lacharité; K.R. Hayes; G. Wood; K. Evans; D. Hatton MacDonald; J. Dambacher; R.H. Bustamante; R. Abbassi; P. Fidelman; et al. (Marine Policy, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Diversity and composition of mixed-ploidy unisexual salamander assemblages reflect the key influence of host species - Evan A. Bare; Jim P. Bogart; Chris Wilson; Dennis L. Murray; Thomas J. Hossie (Oecologia, 2023)

Characterizing the trophy hunting debate on Twitter - Luke Christopher Evans; Matthew P. Greenwell; Victoria L. Boult; Thomas Frederick Johnson (Conservation Biology, 2023)
Social media is an arena of debate for contentious political and social topics. One conservation topic debated online is the acceptability of trophy hunting, a debate that has implications for national and international policy. We used a mixed‐methods approach (grounded theory and quantitative clustering) to identify themes in the trophy hunting debate on Twitter. We examined commonly co‐occurring categories that describe people's stances on trophy hunting. We identified 12 categories and 4 preliminary archetypes opposing trophy hunting— activism , scientific , condemning , and objecting —whose opposition derived from different moral reasoning. Few tweets (22) in our sample of 500 supported trophy hunting, whereas 350 opposed it. The debate was hostile; 7% of tweets in our sample were categorized as abusive. Online debates can be unproductive, and our findings may be important for stakeholders wishing to effectively engage in the trophy hunting debate on Twitter. More generally, we contend that because social media is increasingly influential, it is important to formally contextualize public responses to contentious conservation topics in order to aid communication of conservation evidence and to integrate diverse public perspectives in conservation practice.

MHC class II genes mediate susceptibility and resistance to coronavirus infections in bats - Dominik W. Schmid; Magdalena Meyer; Kerstin Wilhelm; Tatiana Tilley; Thomas Link‐Hessing; Ramona Fleischer; Ebenezer K. Badu; Evans Ewald Nkrumah; Samuel Kingsley Oppong; Nina Schwensow; Marco Tschapka; Heather J. Baldwin; et al. (Molecular Ecology, 2023)
Understanding the immunogenetic basis of coronavirus (CoV) susceptibility in major pathogen reservoirs, such as bats, is central to inferring their zoonotic potential. Members of the cryptic Hipposideros bat species complex differ in CoV susceptibility, but the underlying mechanisms remain unclear. The genes of the major histocompatibility complex (MHC) are the best understood genetic basis of pathogen resistance, and differences in MHC diversity are one possible reason for asymmetrical infection patterns among closely related species. Here, we aimed to link asymmetries in observed CoV (CoV‐229E, CoV‐2B and CoV‐2Bbasal) susceptibility to immunogenetic differences amongst four Hipposideros bat species. From the 2072 bats assigned to their respective species using the mtDNA cytochrome b gene, members of the most numerous and ubiquitous species, Hipposideros caffer D , were most infected with CoV‐229E and SARS‐related CoV‐2B. Using a subset of 569 bats, we determined that much of the existent allelic and functional (i.e. supertype) MHC DRB class II diversity originated from common ancestry. One MHC supertype shared amongst all species, ST12, was consistently linked to susceptibility with CoV‐229E, which is closely related to the common cold agent HCoV‐229E, and infected bats and those carrying ST12 had a lower body condition. The same MHC supertype was connected to resistance to CoV‐2B, and bats with ST12 were less likely be co‐infected with CoV‐229E and CoV‐2B. Our work suggests a role of immunogenetics in determining CoV susceptibility in bats. We advocate for the preservation of functional genetic and species diversity in reservoirs as a means of mitigating the risk of disease spillover.

Effectiveness of a water-vending kiosk intervention toward household water quality and surveyed water security in Freetown, Sierra Leone - Matthew Falcone; Carlo Salvinelli; Mohamed Bah; Evan Thomas (Science of The Total Environment, 2023)

Applying climate reparative finance toward water security - Evan Thomas; Jean Ntazinda; Styvers Kathuni (Science of The Total Environment, 2023)

Exploring the landscape of controlled environment agriculture research: A systematic scoping review of trends and topics - Ajwal Dsouza; Lenore Newman; Thomas Graham; Evan D.G. Fraser (Agricultural Systems, 2023)

Lipid biomarker comparison of relict and active microbial mats from the McMurdo Ice Shelf, Antarctica - Juliana K. Drozd; Thomas W. Evans; Roger E. Summons (Organic Geochemistry, 2023)

Is closing the agricultural yield gap a “risky” endeavor? - Nicolas Gatti; Michael Cecil; Kathy Baylis; Lyndon Estes; Jordan Blekking; Thomas Heckelei; Noemi Vergopolan; Tom Evans (Agricultural Systems, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Protected areas support more species than unprotected areas in Great Britain, but lose them equally rapidly - Rob Cooke; Francesca Mancini; Robin J. Boyd; Karl L. Evans; Anna Shaw; Thomas J. Webb; Nick J.B. Isaac (Biological Conservation, 2023)

Assessing associations between residential proximity to greenspace and birth defects in the National Birth Defects Prevention Study - Kari A. Weber; Wei Yang; Suzan L. Carmichael; R. Thomas Collins; Thomas J. Luben; Tania A. Desrosiers; Tabassum Z. Insaf; Mimi T. Le; Shannon Pruitt Evans; Paul A. Romitti; Mahsa M. Yazdy; Wendy N. Nembhard; et al. (Environmental Research, 2023)

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Using ecological networks to answer questions in global biogeography and ecology - Fredric M. Windsor; Johan van den Hoogen; Thomas W. Crowther; Darren M. Evans (Journal of Biogeography, 2023)
Ecological networks have classically been studied at site and landscape scales, yet recent efforts have been made to collate these data into global repositories. This offers an opportunity to integrate and upscale knowledge about ecological interactions from local to global scales to gain enhanced insights from the mechanistic information provided by these data. By drawing on existing research investigating patterns in ecological interactions at continental to global scales, we show how data on ecological networks, collected at appropriate scales, can be used to generate an improved understanding of many aspects of ecology and biogeography—for example, species distribution modelling, restoration ecology and conservation. We argue that by understanding the patterns in the structure and function of ecological networks across scales, it is possible to enhance our understanding of the natural world.

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

An assessment of the environmental and socio-economic impacts of alien rabbits and hares - Tom Allmert; Jonathan M. Jeschke; Thomas Evans (Ambio, 2022)
Directly comparable data on the environmental and socio-economic impacts of alien species informs the effective prioritisation of their management. We used two frameworks, the Environmental Impact Classification for Alien Taxa (EICAT) and Socio-Economic Impact Classification for Alien Taxa (SEICAT), to create a unified dataset on the severity and type of impacts caused by alien leporids (rabbits and hares). Literature was reviewed to collate impact data, which was categorised following EICAT and SEICAT guidelines. We aimed to use these data to identify: (1) alien leporid species with severe impacts, (2) their impact mechanisms, (3) the native species and local communities vulnerable to impacts and (4) knowledge gaps. Native species from a range of taxonomic groups were affected by environmental impacts which tended to be more damaging than socio-economic impacts. Indirect environmental impacts were particularly damaging and underreported. No impact data were found for several alien leporid species.

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

The C-BIG Repository: an Institution-Level Open Science Platform - Samir Das; Rida Abou-Haidar; Henri Rabalais; Sonia Denise Lai Wing Sun; Zaliqa Rosli; Krishna Chatpar; Marie-Noëlle Boivin; Mahdieh Tabatabaei; Christine Rogers; Melanie Legault; Derek Lo; Clotilde Degroot; et al. (Neuroinformatics, 2022)
In January 2016, the Montreal Neurological Institute-Hospital (The Neuro) declared itself an Open Science organization. This vision extends beyond efforts by individual scientists seeking to release individual datasets, software tools, or building platforms that provide for the free dissemination of such information. It involves multiple stakeholders and an infrastructure that considers governance, ethics, computational resourcing, physical design, workflows, training, education, and intra-institutional reporting structures. The C-BIG repository was built in response as The Neuro’s institutional biospecimen and clinical data repository, and collects biospecimens as well as clinical, imaging, and genetic data from patients with neurological disease and healthy controls. It is aimed at helping scientific investigators, in both academia and industry, advance our understanding of neurological diseases and accelerate the development of treatments. As many neurological diseases are quite rare, they present several challenges to researchers due to their small patient populations. Overcoming these challenges required the aggregation of datasets from various projects and locations. The C-BIG repository achieves this goal and stands as a scalable working model for institutions to collect, track, curate, archive, and disseminate multimodal data from patients. In November 2020, a Registered Access layer was made available to the wider research community at https://cbigr-open.loris.ca , and in May 2021 fully open data will be released to complement the Registered Access data. This article outlines many of the aspects of The Neuro’s transition to Open Science by describing the data to be released, C-BIG’s full capabilities, and the design aspects that were implemented for effective data sharing.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Population genetic structure of a broadcast‐spawning coral across a tropical–temperate transition zone reveals regional differentiation and high‐latitude reef isolation - Richard D. Evans; Luke Thomas; W. Jason Kennington; Nicole M. Ryan; Nerida G. Wilson; Zoe Richards; Ryan J. Lowe; Chenae Tuckett (Journal of Biogeography, 2021)
Aim Genetic connectivity is a key component of species resilience to climate change in terms of recovery capacity following disturbance and capacity to disperse to novel locations as the climate warms and isotherms shift poleward. We aimed to strengthen our understanding of resilience in this context by characterizing patterns of connectivity and genetic diversity in a broadcast spawning coral across a tropical–temperate transition zone. We hypothesize genetic differentiation between tropical and temperate populations and decreasing genetic diversity with higher latitudes. Location Western Australia (WA). Taxon Turbinaria species complex. Turbinaria ‘reniformis’ Oken, 1815 (Scleractinia: Dendrophylliidae). Methods A total of 930 target corals were sampled from 10 locations between 13 and 32° latitude spanning a 9°C mean temperature range. In situ species identification of T . reniformis is hindered by morphological plasticity and homoplasy with sister species. We combined Sanger sequencing of two mitochondrial DNA markers and high‐throughput genotyping by sequencing (GBS) to isolate a single genetic Turbinaria lineage from our dataset through which patterns of genetic flow and diversity along the WA coastline could be explored using population‐ and individual‐based clustering analyses. Results Mitochondrial DNA sequence variation was low among Turbinaria samples and could not resolve individual species. Using GBS, we identified three genetically distinct lineages. Subsequent analyses within one of these lineages revealed strong spatial subdivision with 2–3 genetic clusters. While temperate populations were genetically diverged from more tropical sites, we did not observe declines in genetic diversity with latitude. Main conclusions Tropical populations of T . ‘reniformis’ in Western Australia exhibit strong genetic connectivity, which extends to a southern limit at sub‐tropical Shark Bay. Temperate populations are genetically isolated from their tropical counterparts but have relatively high genetic diversity. While the maintenance of genetic variation in temperate populations may provide some resilience to future climate scenarios, their isolation may increase their vulnerability.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Surveillance recommendations for DICER1 pathogenic variant carriers: a report from the SIOPE Host Genome Working Group and CanGene-CanVar Clinical Guideline Working Group - Jette J. Bakhuizen; Helen Hanson; Karin van der Tuin; Fiona Lalloo; Marc Tischkowitz; Karin Wadt; Marjolijn C. J. Jongmans; Beate B. Dörgeloh; Roula A. Farah; Stavros Glentis; Lisa Golmard; Juliane Hoyer; et al. (Familial Cancer, 2021)
DICER1 syndrome is a rare genetic disorder that predisposes to a wide spectrum of tumors. Developing surveillance protocols for this syndrome is challenging because uncertainty exists about the clinical efficacy of surveillance, and appraisal of potential benefits and harms vary. In addition, there is increasing evidence that germline DICER1 pathogenic variants are associated with lower penetrance for cancer than previously assumed. To address these issues and to harmonize DICER1 syndrome surveillance programs within Europe, the Host Genome Working Group of the European branch of the International Society of Pediatric Oncology (SIOPE HGWG) and Clinical Guideline Working Group of the CanGene-CanVar project in the United Kingdom reviewed current surveillance strategies and evaluated additional relevant literature. Consensus was achieved for a new surveillance protocol and information leaflet that informs patients about potential symptoms of DICER1 -associated tumors. The surveillance protocol comprises a minimum program and an extended version for consideration. The key recommendations of the minimum program are: annual clinical examination from birth to age 20 years, six-monthly chest X-ray and renal ultrasound from birth to age 6 years, and thyroid ultrasound every 3 years from age 8 to age 40 years. The surveillance program for consideration comprises additional surveillance procedures, and recommendations for DICER1 pathogenic variant carriers outside the ages of the surveillance interval. Patients have to be supported in choosing the surveillance program that best meets their needs. Prospective evaluation of the efficacy and patient perspectives of proposed surveillance recommendations is required to expand the evidence base for DICER1 surveillance protocols.

Quantifying the global threat to native birds from predation by non‐native birds on small islands - Thomas Evans (Conservation Biology, 2021)
Although invasive non‐native species can adversely affect biodiversity in many ways, predation of native species by non‐native species on islands can be severely damaging. Results of numerous studies document non‐native birds preying on birds on islands, but our understanding of the number and type of species affected has been limited by the lack of a global review of these impacts. I identified the non‐native bird species that have been recorded preying on birds, the locations where this predation occurred, and the bird species affected. Because the impacts of non‐native birds can be particularly severe on small islands, I then identified the islands 2 around the world that are occupied by predatory non‐native birds. By taking into account their life‐history traits and predation history, I also identified the near‐threatened and threatened bird species on these islands that they may prey on. The results indicated that predation by non‐native birds was primarily a concern for threatened bird conservation on small islands; almost all predation impacts (91%) on near‐threatened and threatened birds were recorded on islands, and median island size was 106 km 2 . I also found non‐native bird predation was a poorly known and widespread potential threat to avian biodiversity; worldwide, 194 islands of 2 were occupied by predatory non‐native birds, but information on their impacts was unavailable for most of these islands. On them, where the impacts of non‐native species can be severe, non‐native birds may be preying on approximately 6% of the world's near‐threatened and threatened bird species. Four non‐native bird species I identified have been successfully eradicated from islands. If they were eradicated from the small islands they occupy, 70% of the near‐threatened and threatened bird species I identified would no longer be affected by nest predation by non‐native birds on small islands.

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Assessment of Flavobacterium psychrophilum ‐associated mortality in Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) - Timothy J. Bruce; Jie Ma; Evan M. Jones; Brent M. Vuglar; Luke P. Oliver; Christopher Knupp; Thomas P. Loch; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Salmonid diseases caused by infections of Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, remain difficult to manage as novel, pathogenic strains continue to emerge in aquaculture settings globally. To date, much of the research regarding treatment options and vaccine development has focused on rainbow trout ( Oncorhynchus mykiss ), but other inland‐reared salmonids are also impacted by this Gram‐negative bacterium. As such, Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) were injection‐challenged with a variety of previously reported F. psychrophilum strains isolated from disease diagnostic cases in salmonids, as well as a standard and well‐studied F. psychrophilum strain (CSF 259–93) known to be virulent in rainbow trout. In three separate virulence assessments (Trials A, B and C), strains US063 (isolated from lake trout; Salvelinus namaycush ) and US149 (isolated from Atlantic salmon) caused a significantly higher cumulative per cent mortality (CPM) relative to other strains in Atlantic salmon ( p p =.008) and B (CPM 96% ± 2.3% vs. 81.33% ± 4.8%, p =.014). Trial C used a lower dose (1.86 × 10 8 CFU/mL) for US149, resulting in a lower mortality (78.67% ± 9.33%) relative to Trials A and B. CSF259‐93 did not cause significant mortality in any trials. In brook trout, the strain 03–179 (originally isolated from steelhead trout; Oncorhynchus mykiss ) was significantly more virulent than any other (CPM 100% ± 0%, p F. psychrophilum virulence testing in Atlantic salmon and brook trout, demonstrating the high virulence of US063 and US149 for these salmonid species. This information is applicable for the development of therapeutics and vaccines against F . psychrophilum infections and demonstrates the reproducibility of the experimental challenge model.

Amenity Migration and Public Lands: Rise of the Protected Areas - Evan Hjerpe; Anwar Hussain; Thomas Holmes (Environmental Management, 2020)

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Global variation in the availability of data on the environmental impacts of alien birds - Thomas Evans; Tim M. Blackburn (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Temperature dependence of parasitic infection and gut bacterial communities in bumble bees - Evan C. Palmer‐Young; Lyna Ngor; Rodrigo Burciaga Nevarez; Jason A. Rothman; Thomas R. Raffel; Quinn S. McFrederick (Environmental Microbiology, 2019)
Summary High temperatures (e.g., fever) and gut microbiota can both influence host resistance to infection. However, effects of temperature‐driven changes in gut microbiota on resistance to parasites remain unexplored. We examined the temperature dependence of infection and gut bacterial communities in bumble bees infected with the trypanosomatid parasite Crithidia bombi . Infection intensity decreased by over 80% between 21 and 37°C. Temperatures of peak infection were lower than predicted based on parasite growth in vitro , consistent with mismatches in thermal performance curves of hosts, parasites and gut symbionts. Gut bacterial community size and composition exhibited slight but significant, non‐linear, and taxon‐specific responses to temperature. Abundance of total gut bacteria and of Orbaceae, both negatively correlated with infection in previous studies, were positively correlated with infection here. Prevalence of the bee pathogen‐containing family Enterobacteriaceae declined with temperature, suggesting that high temperature may confer protection against diverse gut pathogens. Our results indicate that resistance to infection reflects not only the temperature dependence of host and parasite performance, but also temperature‐dependent activity of gut bacteria. The thermal ecology of gut parasite‐symbiont interactions may be broadly relevant to infectious disease, both in ectothermic organisms that inhabit changing climates, and in endotherms that exhibit fever‐based immunity.

Optimal central place foraging flights in relation to wind - Thomas Alerstam; Johan Bäckman; Tom J. Evans (Journal of Ornithology, 2019)

Intercomparison of machine learning methods for statistical downscaling: the case of daily and extreme precipitation - Thomas Vandal; Evan Kodra; Auroop R. Ganguly (Theoretical and Applied Climatology, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Global spread of the German cockroach, Blattella germanica - Qian Tang; Thomas Bourguignon; Luc Willenmse; Eliane De Coninck; Theodore Evans (Biological Invasions, 2019)

Extreme copy number variation at a tRNA ligase gene affecting phenology and fitness in yellow monkeyflowers - Thomas C. Nelson; Patrick J. Monnahan; Mariah K. McIntosh; Kayli Anderson; Evan MacArthur‐Waltz; Findley R. Finseth; John K. Kelly; Lila Fishman (Molecular Ecology, 2019)
Copy number variation ( CNV ) is a major part of the genetic diversity segregating within populations, but remains poorly understood relative to single nucleotide variation. Here, we report on a tRNA ligase gene (Migut.N02091; RLG 1a) exhibiting unprecedented, and fitness‐relevant, CNV within an annual population of the yellow monkeyflower Mimulus guttatus . RLG 1a variation was associated with multiple traits in pooled population sequencing (PoolSeq) scans of phenotypic and phenological cohorts. Resequencing of inbred lines revealed intermediate‐frequency three‐copy variants of RLG 1a ( trip+; 5/35 = 14%), and trip+ lines exhibited elevated RLG 1a expression under multiple conditions. trip+ carriers, in addition to being over‐represented in late‐flowering and large‐flowered PoolSeq populations, flowered later under stressful conditions in a greenhouse experiment ( p RLG 1a variant ( high+ ) that carries 250–300 copies of RLG 1a totalling ~5.7 Mb (20–40% of a chromosome). In the progeny of a high+ carrier, Mendelian segregation of diagnostic alleles and qPCR ‐based copy counts indicate that high+ is a single tandem array unlinked to the single‐copy RLG 1a locus. In the wild, high+ carriers had highest fitness in two particularly dry and/or hot years (2015 and 2017; both p CNV type in a lush year (2016: p CNV s affecting phenological traits in a wild population, suggest that plant tRNA ligases mediate stress‐responsive life‐history traits, and introduce a novel system for investigating the molecular mechanisms of gene amplification.

The evolution of lamprey (Petromyzontida) life history and the origin of metamorphosis - Thomas M. Evans; Philippe Janvier; Margaret F. Docker (Reviews in Fish Biology and Fisheries, 2018)

Ice margin oscillations during deglaciation of the northern Irish Sea Basin - R. C. Chiverrell; R. K. Smedley; D. Small; C. K. Ballantyne; M. J. Burke; S. L. Callard; C. D. Clark; G. A. T. Duller; D. J. A. Evans; D. Fabel; K. van Landeghem; S. Livingstone; et al. (Journal of Quaternary Science, 2018)
We present a new chronology to constrain ice‐margin retreat in the northern Irish Sea Basin. Estimates on the timing of ice thinning derived from surface exposure ages for boulders from the summits of the Isle of Man and south‐west Cumbria suggest that ice thinning was commensurate with the rapid retreat that followed the short‐lived advance of the Irish Sea Ice Stream (ISIS) to maximum limits in the Celtic Sea. This ice retreat in the northern Irish Sea Basin was fastest at 20 ka in response to a wider calving margin, but slowed as ice stabilized and oscillated against the Isle of Man. We provide the first age constraints for the Scottish Readvance (19.2–18.2 ka) and demonstrate that it was a potentially regional event across the Isle of Man and Cumbrian lowlands not linked with Heinrich Event 1. After the Scottish Readvance, the ice front retreated northwards towards the Southern Uplands of Scotland at the same time as climate north of ∼45°N warmed in response to summer insolation. This sequence demonstrates the importance of internal dynamics in controlling ice retreat rates in the Irish Sea, but also that deglaciation of the northern Irish Sea Basin was a response to climate warming.

Regional Simulations of Loblolly Pine Productivity with CO2 Enrichment and Changing Climate Scenarios - Harold E Burkhart; Evan B Brooks; Heather Dinon-Aldridge; Charles O Sabatia; Nabin Gyawali; Randolph H Wynne; Valerie A Thomas (Forest Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Roles for scientific societies to engage with conservation policy - Sarah E. Reed; Sarah L. Thomas; Angela T. Bednarek; Dominick A. DellaSala; Megan C. Evans; Carolyn Lundquist; Michael B. Mascia; Tsitsi Y. McPherson; James E.M. Watson (Conservation Biology, 2018)

Geotourism in an Industrial Setting: the South Wales Coalfield Geoheritage Network - Benjamin G. Evans; Christopher J. Cleal; Barry A. Thomas (Geoheritage, 2018)

Conserving threatened riparian ecosystems in the American West: Precipitation gradients and river networks drive genetic connectivity and diversity in a foundation riparian tree ( Populus angustifolia ) - Helen M. Bothwell; Samuel A. Cushman; Scott A. Woolbright; Erika I. Hersch‐Green; Luke M. Evans; Thomas G. Whitham; Gerard J. Allan (Molecular Ecology, 2017)
Gene flow is an evolutionary process that supports genetic connectivity and contributes to the capacity of species to adapt to environmental change. Yet, for most species, little is known about the specific environmental factors that influence genetic connectivity, or their effects on genetic diversity and differentiation. We used a landscape genetic approach to understand how geography and climate influence genetic connectivity in a foundation riparian tree ( Populus angustifolia ), and their relationships with specieswide patterns of genetic diversity and differentiation. Using multivariate restricted optimization in a reciprocal causal modelling framework, we quantified the relative contributions of riparian network connectivity, terrestrial upland resistance and climate gradients on genetic connectivity. We found that (i) all riparian corridors, regardless of river order, equally facilitated connectivity, while terrestrial uplands provided 2.5× more resistance to gene flow than riparian corridors. (ii) Cumulative differences in precipitation seasonality and precipitation of the warmest quarter were the primary climatic factors driving genetic differentiation; furthermore, maximum climate resistance was 45× greater than riparian resistance. (iii) Genetic diversity was positively correlated with connectivity ( R 2 = 0.3744, p = .0019), illustrating the utility of resistance models for identifying landscape conditions that can support a species' ability to adapt to environmental change. From these results, we present a map highlighting key genetic connectivity corridors across P. angustifolia's range that if disrupted could have long‐term ecological and evolutionary consequences. Our findings provide recommendations for conservation and restoration management of threatened riparian ecosystems throughout the western USA and the high biodiversity they support.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Restricted gene flow and local adaptation highlight the vulnerability of high‐latitude reefs to rapid environmental change - Luke Thomas; W. Jason Kennington; Richard D. Evans; Gary A. Kendrick; Michael Stat (Global Change Biology, 2017)
Global climate change poses a serious threat to the future health of coral reef ecosystems. This calls for management strategies that are focused on maximizing the evolutionary potential of coral reefs. Fundamental to this is an accurate understanding of the spatial genetic structure in dominant reef‐building coral species. In this study, we apply a genotyping‐by‐sequencing approach to investigate genome‐wide patterns of genetic diversity, gene flow, and local adaptation in a reef‐building coral, Pocillopora damicornis, across 10 degrees of latitude and a transition from temperate to tropical waters. We identified strong patterns of differentiation and reduced genetic diversity in high‐latitude populations. In addition, genome‐wide scans for selection identified a number of outlier loci putatively under directional selection with homology to proteins previously known to be involved in heat tolerance in corals and associated with processes such as photoprotection, protein degradation, and immunity. This study provides genomic evidence for both restricted gene flow and local adaptation in a widely distributed coral species, and highlights the potential vulnerability of leading‐edge populations to rapid environmental change as they are locally adapted, reproductively isolated, and have reduced levels of genetic diversity.

Neuromuscular adaptations to sprint interval training and the effect of mammalian omega-3 fatty acid supplementation - Evan J. H. Lewis; Frédéric Stucky; Peter W. Radonic; Adam H. Metherel; Thomas M. S. Wolever; Greg D. Wells (European Journal of Applied Physiology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A fluorescence-based quantitative real-time PCR assay for accurate Pocillopora damicornis species identification - Luke Thomas; Michael Stat; Richard D. Evans; W. Jason Kennington (Coral Reefs, 2016)

Population structure of the German cockroach, Blattella germanica, shows two expansions across China - Qian Tang; Hong Jiang; Yangsheng Li; Thomas Bourguignon; Theodore Alfred Evans (Biological Invasions, 2016)

Controls on the processing and fate of terrestrially-derived organic carbon in aquatic ecosystems: synthesis of special issue - Chris D. Evans; David N. Thomas (Aquatic Sciences, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Erratum to: Development of polymorphic microsatellite markers for the microendemic pupfishes Cyprinodon julimes and C. pachycephalus - Evan W. Carson; Rochelle R. Beasley; Kenneth L. Jones; Stacey L. Lance; Ma de Lourdes Lozano-Vilano; Lilia Vela-Valladares; Iris Banda-Villanueva; Thomas F. Turner; Mauricio De la Maza-Benignos (Conservation Genetics Resources, 2015)

Cardiac fibroblasts: from development to heart failure - Thomas Moore-Morris; Nuno Guimarães-Camboa; Katherine E. Yutzey; Michel Pucéat; Sylvia M. Evans (Journal of Molecular Medicine, 2015)

Characterizing avian survival along a rural‐to‐urban land use gradient - Brian S. Evans; Thomas B. Ryder; Robert Reitsma; Allen H. Hurlbert; Peter P. Marra (Ecology, 2015)
Many avian species persist in human‐dominated landscapes; however, little is known about the demographic consequences of urbanization in these populations. Given that urban habitats introduce novel benefits (e.g., anthropogenic resources) and pressures (e.g., mortality risks), conflicting mechanisms have been hypothesized to drive the dynamics of urban bird populations. Top‐down processes such as predation predict reduced survivorship in suburban and urban habitats, whereas bottom‐up processes, such as increased resource availability, predict peak survival in suburban habitats. In this study, we use mark–recapture data of seven focal species encountered between 2000 and 2012 to test hypotheses about the processes that regulate avian survival along an urbanization gradient in greater Washington, D.C., USA. American Robin, Gray Catbird, Northern Cardinal, and Song Sparrow exhibited peak survival at intermediate and upper portions of the rural‐to‐urban gradient; this pattern supports the hypothesis that bottom‐up processes (e.g., resource availability) can drive patterns of avian survival in some species. In contrast, Carolina Chickadee showed no response and Carolina and House Wren showed a slightly negative response to urban land cover. These contrasting results underscore the need for comparative studies documenting the mechanisms that drive demography and how those factors differentially affect urban adapted and urban avoiding species.

A development-based approach to global climate policy - Susan Spierre Clark; Thomas P. Seager; Evan Selinger (Environment Systems and Decisions, 2015)

Health effects of fine particulate matter in life cycle impact assessment: findings from the Basel Guidance Workshop - Peter Fantke; Olivier Jolliet; John S. Evans; Joshua S. Apte; Aaron J. Cohen; Otto O. Hänninen; Fintan Hurley; Matti J. Jantunen; Michael Jerrett; Jonathan I. Levy; Miranda M. Loh; Julian D. Marshall; et al. (The International Journal of Life Cycle Assessment, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

A counterweight is not necessary to implement simple, natural and comfortable single-leg cycle training - Thomas E. Dolmage; Rachael A. Evans; Roger S. Goldstein (European Journal of Applied Physiology, 2014)

Defining the Impact of Non‐Native Species - JONATHAN M. JESCHKE; SVEN BACHER; TIM M. BLACKBURN; JAIMIE T. A. DICK; FRANZ ESSL; THOMAS EVANS; MIRIJAM GAERTNER; PHILIP E. HULME; INGOLF KÜHN; AGATA MRUGAŁA; JAN PERGL; PETR PYŠEK; et al. (Conservation Biology, 2014)
Non‐native species cause changes in the ecosystems to which they are introduced. These changes, or some of them, are usually termed impacts; they can be manifold and potentially damaging to ecosystems and biodiversity. However, the impacts of most non‐native species are poorly understood, and a synthesis of available information is being hindered because authors often do not clearly define impact. We argue that explicitly defining the impact of non‐native species will promote progress toward a better understanding of the implications of changes to biodiversity and ecosystems caused by non‐native species; help disentangle which aspects of scientific debates about non‐native species are due to disparate definitions and which represent true scientific discord; and improve communication between scientists from different research disciplines and between scientists, managers, and policy makers. For these reasons and based on examples from the literature, we devised seven key questions that fall into 4 categories: directionality, classification and measurement, ecological or socio‐economic changes, and scale. These questions should help in formulating clear and practical definitions of impact to suit specific scientific, stakeholder, or legislative contexts. Definiendo el Impacto de las Especies No‐Nativas

Vascular Structure Design of an Artificial Tree for Microbial Cell Cultivation and Biofuel Production - Thomas E. Murphy; Evan Fleming; Halil Berberoglu (Transport in Porous Media, 2014)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

Conservation genetic assessment of the critically endangered Julimes pupfish, Cyprinodon julimes - Evan W. Carson; Mauricio De la Maza-Benignos; María de Lourdes Lozano-Vilano; Lilia Vela-Valladares; Iris Banda-Villanueva; Thomas F. Turner (Conservation Genetics, 2014)

Glycerophospholipid Analysis of Eastern Red Bat (Lasiurus Borealis) Hair by Electrospray Ionization Tandem Mass Spectrometry - Evan L. Pannkuk; Liam P. Mcguire; David F. Gilmore; Brett J. Savary; Thomas S. Risch (Journal of Chemical Ecology, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

Development of polymorphic microsatellite markers for the microendemic pupfishes Cyprinodon julimes and C. pachycephalus - Evan W. Carson; Rochelle R. Beasley; Kenneth L. Jones; Stacey L. Lance; Ma de Lourdes Lozano-Vilano; Lilia Vela-Valladares; Iris Banda-Villanueva; Thomas F. Turner; Mauricio De la Maza-Benignos (Conservation Genetics Resources, 2013)

Investigating the potential use of aerial line transect surveys for estimating polar bear abundance in sea ice habitats: A case study for the Chukchi Sea - Ryan M. Nielson; Thomas J. Evans; Michelle Bourassa Stahl (Marine Mammal Science, 2013)
The expense of traditional capture‐recapture methods, interest in less invasive survey methods, and the circumpolar decline of polar bear ( Ursus maritimus ) habitat require evaluation of alternative methods for monitoring polar bear populations. Aerial line transect distance sampling (DS) surveys are thought to be a promising monitoring tool. However, low densities and few observations during a survey can result in low precision, and logistical constraints such as heavy ice and fuel and safety limitations may restrict survey coverage. We used simulations to investigate the accuracy and precision of, DS for estimating polar bear abundance in sea ice habitats, using the Chukchi Sea subpopulation as an example. Simulation parameters were informed from a recent pilot survey. Predictions from a resource selection model were used for stratification, and we compared two ratio estimators to account for areas that cannot be sampled. The ratio estimator using predictions of resource selection by polar bears allowed for extrapolation beyond sampled areas and provided results with low bias and CVs ranging from 21% to 36% when abundance was >1,000. These techniques could be applied to other DS surveys to allocate effort and potentially extrapolate estimates to include portions of the landscape that are logistically impossible to survey.

Rapid Loss of Cambodia's Grasslands - Charlotte E. Packman; Thomas N. E. Gray; Nigel J. Collar; Tom D. Evans; Robert N. Van Zalinge; Son Virak; Andrew A. Lovett; Paul M. Dolman (Conservation Biology, 2013)

A Comparison of the Prevalence of Lead-Contaminated Imported Chinese Ceramic Dinnerware Purchased Inside Versus Outside Philadelphia's Chinatown - Thomas Gilmore; Gerald F. O’Malley; Wayne Bond Lau; David R. Vann; Adam Bromberg; Aaron Martin; Andrea Gibbons; Evan Rimmer (Journal of Medical Toxicology, 2013)

Bayesian modelling the retreat of the Irish Sea Ice Stream - Richard C. Chiverrell; Ian M. Thrasher; Geoffrey S. P. Thomas; Andreas Lang; James D. Scourse; Katrien J. J. van Landeghem; Danny Mccarroll; Chris D. Clark; Colm Ó Cofaigh; David J. A. Evans; Colin K. Ballantyne (Journal of Quaternary Science, 2013)
We present an 8000‐year history spanning 650 km of ice margin retreat for the largest marine‐terminating ice stream draining the former British–Irish Ice Sheet. Bayesian modelling of the geochronological data shows the ISIS expanded 34.0–25.3 ka, accelerating into the Celtic Sea to reach maximum limits 25.3–24.5 ka before a collapse with rapid marginal retreat to the northern Irish Sea Basin (ISB). This retreat was rapid and driven by climatic warming, sea‐level rise, mega‐tidal amplitudes and reactivation of meridional circulation in the North Atlantic. The retreat, though rapid, is uneven, with the stepped retreat pattern possibly a function of the passage of the ice stream between normal and adverse ice bed gradients and changing ice stream geometry. Initially, wide calving margins and adverse slopes encouraged rapid retreat (∼550 m a −1 ) that slowed (∼100 m a −1 ) at the topographic constriction and bathymetric high between southern Ireland and Wales before rates increased (∼200 m a −1 ) across adverse bed slopes and wider and deeper basin configuration in the northern ISB. These data point to the importance of the ice bed slope and lateral extent in predicting the longer‐term (>1000 a) patterns and rates of ice‐marginal retreat during phases of rapid collapse, which has implications for the modelling of projected rapid retreat of present‐day ice streams. Copyright © 2013 John Wiley & Sons, Ltd.

Herbivore host-associated genetic differentiation depends on the scale of plant genetic variation examined - Luke M. Evans; Gerard J. Allan; Nashelly Meneses; Tamara L. Max; Thomas G. Whitham (Evolutionary Ecology, 2013)

Populus hybrid hosts drive divergence in the herbivorous mite, Aceria parapopuli: implications for conservation of plant hybrid zones as essential habitat - Luke M. Evans; Gerard J. Allan; Thomas G. Whitham (Conservation Genetics, 2012)

Relationships between spatio‐temporal environmental and genetic variation reveal an important influence of exogenous selection in a pupfish hybrid zone - EVAN W. CARSON; MICHAEL TOBLER; W. L. MINCKLEY; RYAN J. AINSWORTH; THOMAS E. DOWLING (Molecular Ecology, 2012)
The importance of exogenous selection in a natural hybrid zone between the pupfishes Cyprinodon atrorus and Cyprinodon bifasciatus was tested via spatio‐temporal analyses of environmental and genetic change over winter, spring and summer for three consecutive years. A critical influence of exogenous selection on hybrid zone regulation was demonstrated by a significant relationship between environmental (salinity and temperature) and genetic (three diagnostic nuDNA loci) variation over space and time (seasons) in the Rio Churince system, Cuatro Ciénegas, Mexico. At sites environmentally more similar to parental habitats, the genetic composition of hybrids was stable and similar to the resident parental species, whereas complex admixtures of parental and hybrid genotypic classes characterized intermediate environments, as did the greatest change in allelic and genotypic frequencies across seasons. Within hybrids across the entire Rio Churince system, seasonal changes in allelic and genotypic frequencies were consistent with results from previous reciprocal transplant experiments, which showed C. bifasciatus to suffer high mortality (75%) when exposed to the habitat of C. atrorus in winter (extreme temperature lows and variability) and summer (abrupt salinity change and extreme temperature highs and variability). Although unconfirmed, the distributional limits of C. atrorus and C. atrorus ‐like hybrids appear to be governed by similar constraints (predation or competition). The argument favouring evolutionary significance of hybridization in animals is bolstered by the results of this study, which links the importance of exogenous selection in a contemporary hybrid zone between C. atrorus and C. bifasciatus to previous demonstration of the long‐term evolutionary significance of environmental variation and introgression on the phenotypic diversification Cuatro Ciénegas Cyprinodon .

The relative influences of host plant genotype and yearly abiotic variability in determining herbivore abundance - Luke M. Evans; James S. Clark; Amy V. Whipple; Thomas G. Whitham (Oecologia, 2012)

Effects of cucurbitacins on cell morphology are associated with sensitization of renal carcinoma cells to TRAIL-induced apoptosis - Curtis J. Henrich; Cheryl L. Thomas; Alan D. Brooks; Nancy Lynn Booth; Evan M. Lowery; Richard J. Pompei; James B. McMahon; Thomas J. Sayers (Apoptosis, 2012)

Elevated CO 2 affects photosynthetic responses in canopy pine and subcanopy deciduous trees over 10 years: a synthesis from D uke FACE - David S. Ellsworth; Richard Thomas; Kristine Y. Crous; Sari Palmroth; Eric Ward; Chris Maier; Evan DeLucia; Ram Oren (Global Change Biology, 2012)
Leaf responses to elevated atmospheric CO 2 concentration (C a ) are central to models of forest CO 2 exchange with the atmosphere and constrain the magnitude of the future carbon sink. Estimating the magnitude of primary productivity enhancement of forests in elevated C a requires an understanding of how photosynthesis is regulated by diffusional and biochemical components and up‐scaled to entire canopies. To test the sensitivity of leaf photosynthesis and stomatal conductance to elevated C a in time and space, we compiled a comprehensive dataset measured over 10 years for a temperate pine forest of P inus taeda , but also including deciduous species, primarily L iquidambar styraciflua . We combined over one thousand controlled‐response curves of photosynthesis as a function of environmental drivers (light, air C a and temperature) measured at canopy heights up to 20 m over 11 years (1996–2006) to generate parameterizations for leaf‐scale models for the D uke free‐air CO 2 enrichment ( FACE ) experiment. The enhancement of leaf net photosynthesis ( A net ) in P . taeda by elevated C a of +200 μmol mol −1 was 67% for current‐year needles in the upper crown in summer conditions over 10 years. Photosynthetic enhancement of P . taeda at the leaf‐scale increased by two‐fold from the driest to wettest growing seasons. Current‐year pine foliage A net was sensitive to temporal variation, whereas previous‐year foliage A net was less responsive and overall showed less enhancement (+30%). Photosynthetic downregulation in overwintering upper canopy pine needles was small at average leaf N ( N area ), but statistically significant. In contrast, co‐dominant and subcanopy L . styraciflua trees showed A net enhancement of 62% and no A net – N area adjustments. Various understory deciduous tree species showed an average A net enhancement of 42%. Differences in photosynthetic responses between overwintering pine needles and subcanopy deciduous leaves suggest that increased C a has the potential to enhance the mixed‐species composition of planted pine stands and, by extension, naturally regenerating pine‐dominated stands.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

Ecological genetics of invasive alien species - L.-J. Lawson Handley; A. Estoup; D. M. Evans; C. E. Thomas; E. Lombaert; B. Facon; A. Aebi; H. E. Roy (BioControl, 2011)

Clinical, laboratory, and neuroimaging characteristics of fatigue in HIV-infected individuals - Giovanni Schifitto; Lijuan Deng; Tzu-min Yeh; Scott R. Evans; Thomas Ernst; Jianhui Zhong; David Clifford (Journal of NeuroVirology, 2011)

Accounting for human behavior, local conditions and organizational constraints in humanitarian development models - Evan Thomas; Bernard Amadei (Environment, Development and Sustainability, 2010)

Impact of wastewater fouling on contact angle - Evan Thomas; Dean Muirhead (Biofouling, 2009)

Second Generation Biofuels: High-Efficiency Microalgae for Biodiesel Production - Peer M. Schenk; Skye R. Thomas-Hall; Evan Stephens; Ute C. Marx; Jan H. Mussgnug; Clemens Posten; Olaf Kruse; Ben Hankamer (BioEnergy Research, 2008)

Trace Element Concentrations in Livers of Polar Bears from Two Populations in Northern and Western Alaska - Kurunthachalam Kannan; Tetsuro Agusa; Thomas J. Evans; Shinsuke Tanabe (Archives of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Resistance to infection by stealth: Brassica napus (winter oilseed rape) and Pyrenopeziza brassicae (light leaf spot) - E. F. Boys; S. E. Roques; A. M. Ashby; N. Evans; A. O. Latunde-Dada; J. E. Thomas; J. S. West; B. D. L. Fitt (European Journal of Plant Pathology, 2007)

Forest carbon use efficiency: is respiration a constant fraction of gross primary production? - EVAN H. DeLUCIA; JOHN E. DRAKE; RICHARD B. THOMAS; MIQUEL GONZALEZ‐MELER (Global Change Biology, 2007)
Carbon‐use efficiency (CUE), the ratio of net primary production (NPP) to gross primary production (GPP), describes the capacity of forests to transfer carbon (C) from the atmosphere to terrestrial biomass. It is widely assumed in many landscape‐scale carbon‐cycling models that CUE for forests is a constant value of ∼0.5. To achieve a constant CUE, tree respiration must be a constant fraction of canopy photosynthesis. We conducted a literature survey to test the hypothesis that CUE is constant and universal among forest ecosystems. Of the 60 data points obtained from 26 papers published since 1975, more than half reported values of GPP that were not estimated independently from NPP; values of CUE calculated from independent estimates of GPP were greater than those calculated from estimates of GPP derived from NPP. The slope of the relationship between NPP and GPP for all forests was 0.53, but values of CUE varied from 0.23 to 0.83 for different forest types. CUE decreased with increasing age, and a substantial portion of the variation among forest types was caused by differences in stand age. When corrected for age the mean value of CUE was greatest for temperate deciduous forests and lowest for boreal forests. CUE also increased as the ratio of leaf mass‐to‐total mass increased. Contrary to the assumption of constancy, substantial variation in CUE has been reported in the literature. It may be inappropriate to assume that respiration is a constant fraction of GPP as adhering to this assumption may contribute to incorrect estimates of C cycles. A 20% error in current estimates of CUE used in landscape models (i.e. ranging from 0.4 to 0.6) could misrepresent an amount of C equal to total anthropogenic emissions of CO 2 when scaled to the terrestrial biosphere.

A method for quantitative analysis of spatially variable physiological processes across leaf surfaces - Mihai Aldea; Thomas D. Frank; Evan H. DeLucia (Photosynthesis Research, 2007)

Molecular properties of P2X receptors - Jonathan A. Roberts; Catherine Vial; Helen R. Digby; Kelvin C. Agboh; Hairuo Wen; Amelia Atterbury-Thomas; Richard J. Evans (Pflügers Archiv - European Journal of Physiology, 2006)

Comparison of photosynthetic damage from arthropod herbivory and pathogen infection in understory hardwood saplings - Mihai Aldea; Jason G. Hamilton; Joseph P. Resti; Arthur R. Zangerl; May R. Berenbaum; Thomas D. Frank; Evan H. DeLucia (Oecologia, 2006)

Integrated Risk Framework for Onsite Wastewater Treatment Systems - Steven Carroll; Ashantha Goonetilleke; Evan Thomas; Megan Hargreaves; Ray Frost; Les Dawes (Environmental Management, 2006)

Influence of hydrogeographic history and hybridization on the distribution of genetic variation in the pupfishes Cyprinodon atrorus and C. bifasciatus - EVAN W. CARSON; THOMAS E. DOWLING (Molecular Ecology, 2006)
The evolutionary importance of hybridization in animals has been subject of much debate. In this study, we examined the influence of hydrogeographic history and hybridization on the present distribution of nuclear and mitochondrial DNA variation in two pupfish species, Cyprinodon atrorus and Cyprinodon bifasciatus . Results presented here indicate that there has been limited introgression of nuclear genes; however, mtDNA introgression has been substantial, with complete replacement of the C . bifasciatus mitochondrial genome by that of C . atrorus . Subsequent to this replacement, there has been diversification of mitochondrial haplotypes along major geographic regions in the basin. Evidence was also found that mitochondrial replacement follows a predictable, cyclical pattern in this system, with isolation and diversification followed by re‐contact and replacement of C . bifasciatus mitochondrial haplotypes by those of C . atrorus . This pattern is best explained by a combination of a numeric bias towards C . atrorus and mating site selection rather than selection for C . atrorus mitochondrial genome. These results demonstrate the important role hybridization can play in evolution.

First Jurassic Choristodera from Asia - Alexander O. Averianov; Thomas Martin; Susan E. Evans; Aizek A. Bakirov (The Science of Nature, 2006)

Studies on the rust Prospodium tuberculatum , a new classical biological control agent released against the invasive alien weed Lantana camara in Australia. 1. Life-cycle and infection parameters - C. A. Ellison; J. M. Pereira; S. E. Thomas; R. W. Barreto; H. C. Evans (Australasian Plant Pathology, 2006)

Severity, Extent and Persistence of Spatial Yield Variation in Production Fields in the SE US Coastal Plain - E. J. Sadler; D. E. Evans; B. K. Gerwig; J. A. Millen; W. Thomas; P. Fussell (Precision Agriculture, 2005)

Ectomycorrhizal mantles as indicators of hydrology for jurisdictional wetland determinations - Bruce Vasilas; Lenore Vasilas; Jeff Thompson; Al Rizzo; Jeff Fuhrmann; Thomas Evans; John Pesek; Karl Kunkle (Wetlands, 2004)

Taxonomy and biocontrol potential of a new species of Trichoderma from the Amazon basin of South America - Keith A. Holmes; Hans-Josef Schroers; Sarah E. Thomas; Harry C. Evans; Gary J. Samuels (Mycological Progress, 2004)

Visualization-Based Analysis for a Mixed-Inhibition Binary PBPK Model: Determination of Inhibition Mechanism - Kristin K. Isaacs; Marina V. Evans; Thomas R. Harris (Journal of Pharmacokinetics and Pharmacodynamics, 2004)

Patterns of branch permeability with crown depth among loblolly pine families differing in growth rate and crown size - Mauricio Jerez; Thomas J. Dean; Scott D. Roberts; David L. Evans (Trees, 2004)

Spontaneous clearance of high-titer serum HBV DNA and risk of hepatocellular carcinoma in a Chinese population - Rebecca A. Harris; Gang Chen; Wen Yao Lin; Fu Min Shen; W. Thomas London; Alison A. Evans (Cancer Causes & Control, 2003)

The biology and chemistry of land fast ice in the White Sea, Russia?A comparison of winter and spring conditions - Andreas Krell; Caroline Ummenhofer; Gerhard Kattner; Andrei Naumov; Dylan Evans; Gerhard S. Dieckmann; David N. Thomas (Polar Biology, 2003)

Endophytes and mycoparasites associated with an indigenous forest tree, Theobroma gileri, in Ecuador and a preliminary assessment of their potential as biocontrol agents of cocoa diseases - Harry C. Evans; Keith A. Holmes; Sarah E. Thomas (Mycological Progress, 2003)

Understanding Broadscale Wildfire Risks in a Human-Dominated Landscape - Jeffrey P. Prestemon; John M. Pye; David T. Butry; Thomas P. Holmes; D. Evan Mercer (Forest Science, 2002)
Broadscale statistical evaluations of wildfire incidence can answer policy-relevant questions about the effectiveness of microlevel vegetation management and can identify subjects needing further study. A dynamic time series cross-sectional model was used to evaluate the statistical links between forest wildfire and vegetation management, human land use, and climatic factors in Florida counties. Four forest wildfire risk functions were estimated: one for fires regardless of ignition source, and three others for fires of specific ignition sources: arson, lightning, and accident (unintentional anthropogenic). Results suggest that current wildfire risk is negatively related to several years of past wildfire and very recent site prep burning, and risk is positively related to pulpwood removals. The effect of traditional prescribed burning on wildfire risk varies by ignition source. El Niño–Southern Oscillation (ENSO) sea surface temperature (SST) anomalies were also significantly linked to forest wildfire risk, but a measure of the wildland-urban interface was not significant. Although these county-level results hold promise for aggregate risk assessment, modeling at finer spatial and temporal scales might further enhance our understanding of how land managers can best reduce the longer term risk of catastrophic wildfire damages. For. Sci. 48(4):685–693.

The Effect of Pulsed Ultrasound on Mandibular Distraction - Tarek H. El-Bialy; Thomas J. Royston; Richard L. Magin; Carla A. Evans; Abd El-Moneim Zaki; Leon A. Frizzell (Annals of Biomedical Engineering, 2002)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Temperature and Base Sequence Dependence of 2-Aminopurine Fluorescence Bands in Single- and Double-Stranded Oligodeoxynucleotides - Mikako Kawai; Michael J. Lee; Kervin O. Evans; Thomas M. Nordlund (Journal of Fluorescence, 2001)

Transferrin receptor activity and localisation in the rat duodenum - Phillip S. Oates; Carla Thomas; Evan H. Morgan (Pflügers Archiv - European Journal of Physiology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

GFAP-Immunoreactivity following hypothermic forebrain ischemia - Kusum Kumar; Xiaolin Wu; A. Thomas Evans (Metabolic Brain Disease, 1997)

Induction of xylulose-5-phosphate phosphoketolase in a variety of yeasts grown ond-xylose: the key to efficient xylose metabolism - Christopher Thomas Evans; Colin Ratledge (Archives of Microbiology, 1984)